In situ scratch testing and abrasion simulation of WC/Co. (January 2017) - Gee, Mark; Mingard, Ken; Nunn, John; Roebuck, Bryan; Gant, Andrew
Abstract: WC/Co hardmetals are used in many applications where wear resistance is important. However, despite recent work, the microstructural basis of wear is not completely understood. This paper describes the results of in situ scratch experiments carried out with a NPL designed and manufactured microtribometer in which spherically ended diamond indenters were moved under load across polished WC/Co samples to generate damage. The microtribometer was mounted in the chamber of a high resolution SEM so that sequential images and video of the damage generated by repeat scratches could be captured. In the experiments, the effects of changing the number of repeat passes, and whether repeat passes were carried out in the same lateral position over the top of the previous pass or with a random lateral offset to simulate abrasion were also investigated. The results gave valuable information on details of how the damage observed was related to the WC/Co microstructure. A major mechanism of damage, clearly observed in the videos of the damage accumulation appended with this paper, was the progressive fragmentation of WC grains; the movement of the WC fragments could be followed from one pass to the next until they are finally removed from the wear interface as debris. Highlights: Novel in situ microtribology experiments on WC/Co hardmetals are presented. Experiments show evolution of surface damage in tribological contact. Degree of damage is linked to orientation of WC grains in material.